Efektifitas the Safe Delivery App (SDA) secara Blended Learning terhadap Pengetahuan Bidan: Effect of The Safe Delivery App (SDA) by Blended Learning on Midwives' Knowledge - Dwie Yunita Baska; Elly Wahyuni; Wewet Savitri (Poltekkes Kemenkes Palu, 2023)
Instroduction: Globally on the industrial revolution of 4.0 mobile learning (mLearning) tools were familiar and attracted considerable attention for healthcare workers as a means of continuous training. The Safe Delivery App’s innovation (SDA) is a smartphone mLearning app that contains information and skills for trained health workers, can be accessed directly, quckly, and based on evidence-based Basic Emergency Obstetric and Neonatal Care (BEmONC) content. Purpose: This study assessed the effect of the SDA intervention by blended learning on midwives’ knowledge. Methods: The study used a quasi-experimental group pre-and post-test design with control group. The research sample consisted of 48 midwives with randomized sampling grouping through by-wheel trial numbers, timing 3 to 6 month. An independent sample t-test was used to statistically, Confidence interval (Cls) and effect size by Cohen’s d were used. Results: The use of The SDA App has proven to be significantly effective in creasing knowledge, the mean differences before-after 5,39 (SD=2,37); 95% Cl 2,29 ± 4,28, p-value <0,001 and d=1,38 in one of the modules. Conclusion: The SDA App has proven very effective improved the quality of human resources for midwives, hope these benefits will be further disseminated wider by all heatlh cares provider.